PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA PADA SISWA KELAS IV SEKOLAH DASAR - Winda Aulia Br Sembiring; Wahyu Susiloningsih (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2026)
This research is motivated by the low mathematical problem-solving abilities of elementary school students, who still require innovation in the learning process. This study aims to analyze the effect of the implementation of the Problem-Based Learning (PBL) model on the mathematical problem-solving abilities of fourth-grade students in the subject of picture patterns and number patterns at Kepuh Kiriman 1 State Elementary School, Waru. The method used was a quasi-experimental study with a Nonequivalent Control Group Design. The study sample consisted of 50 students divided into two groups: an experimental group and a control group, each consisting of 25 students. The research instrument was a descriptive test that had undergone validity and reliability tests. Data analysis was performed using the Independent Sample t-test after meeting the prerequisite tests for normality and homogeneity. The results showed a significant difference between the two groups. This indicates that the implementation of the Problem-Based Learning model has a positive impact on improving elementary school students' mathematical problem-solving abilities.